Lords of African slavery in reino of Chile. Local Market and Family Patrimony, Valparaíso 1750-1817. (Palimpsesto, 2017)
The study observes the impact of the introduction of African slavery in late colonial Valparaíso, given the geopolitical situation of the port that during this period would consolidate its commercial character, increasing the circulation of people and merchandises in its jurisdiction. Thus, among other consumption goods traded on its coasts, forced migration brought African slavery to the internal commercial circuit of the Río de la Plata, Perú and Chile, so that its elite neighbors participated in the local slave market by developing strategies to preserve the family patrimony by exchanging or inheriting their slave labor. Hence, analyze sales and taxation for this concept, observing the social origin of those interested in this type of trade.
Keywords: African slavery; local market; family patrimony; late colonial Valparaíso